Fitness Exercises As A Means Of Motivation For Physical Education Classes For High School Students - Shkola, Olena; Zhamardiy, Valeriy; Kyzim, Petro; Ramsey, Irina; Zaria, Larisa (My University, 2022)
In the article, fitness aerobics is considered as one of the effective forms that provide the formation of interest and motivation among high school students for physical exercises and health promotion. The purpose of the work is to develop a methodology for using fitness aerobics in physical education classes in physical education classes for high school girls. The study was conducted on the basis of Kharkov Specialized School № 33. The study involved 25 students in grades 10–11. Research methods: analysis of scientific and methodical literature; pedagogical observation; pedagogical experiment; pedagogical testing; methods of mathematical statistics. The method of using fitness aerobics in the physical education classes of high school girls was theoretically substantiated and developed. Improved the content of the planned independent fitness classes, which were used as an additional reserve of motivation and increase weekly physical activity. The data on the use of fitness aerobics to increase the level of physical fitness of high school students and motivation for physical education have been supplemented. The results of the experiment that in comparison with the data at the beginning of the students’ motivation to attend physical education classes had changed. Before the introduction of pedagogical technology, the vast majority of students attended physical education classes to get a positive assessment, then, at the end of the formative experiment, the students went to physical education classes because they liked the style of the lessons and in order to improve their health and level of physical fitness
Fitness Exercises As A Means Of Motivation For Physical Education Classes For High School Students / Olena Shkola, Valeriy Zhamardiy, Petro Kyzim, Irina Ramsey, Larisa Zaria // Journal for Educators, Teachers and Trainers, 2022. – Vol. 13(2). P. 243 –251.
Keywords: fitness aerobics, high school students, physical culture, health, methodology; фітнес-аеробіка, старшокласники, фізична культура, здоров'я, методика